Security Challenges in Implementation of Drone as a Delivery Method in Indonesia - Antonio, Yohanes Adeatma (European Journal of Applied Sciences, 2023)
The application of drone as a method of transportation and delivery has been implemented, however there are still challenges and difficulties faced especially when trying to do it in Indonesia. One of the main reasons for this is the lack of security for drones, either from the physical, privacy, or the drone’s own cyber security. In order to further study the drones’ security problem, a systematic literature review is conducted to provide analysis for the application of drone in the Indonesian industrial context. The study result shows that in addition to drone user behavior problems, there is technical problem that limits the usage of drone in Indonesia. From the research conducted, alternative solutions include having a more thorough laws and regulation concerning drones use and data privacy issues in order for it to be developed further in Indonesia.